SZT2 variants associated with partial epilepsy or epileptic encephalopathy and the genotype-phenotype correlation - Luo, Sheng; Ye, Xing-Guang; Jin, Liang; Li, Huan; He, Yun-Yan; Guan, Bao-Zhu; Gao, Liang-Di; Liang, Xiao-Yu; Wang, Peng-Yu; Lu, Xin-Guo; Yan, Hong-Jun; Li, Bing-Mei; et al. (Frontiers in Molecular Neuroscience, 2023)
Background Recessive SZT2 variants are reported to be associated with developmental and epileptic encephalopathy 18 (DEE-18) and occasionally neurodevelopment abnormalities (NDD) without seizures. This study aims to explore the phenotypic spectrum of SZT2 and the genotype-phenotype correlation. Methods Trios-based whole-exome sequencing was performed in patients with epilepsy. Previously reported SZT2 mutations were systematically reviewed to analyze the genotype-phenotype correlations. Results SZT2 variants were identified in six unrelated cases with heterogeneous epilepsy, including one de novo null variant and five pairs of biallelic variants. These variants had no or low frequencies in controls. All missense variants were predicted to alter the hydron bonds with surrounding residues and/or protein stability. The three patients with null variants exhibited DEE. The patients with biallelic null mutations presented severe DEE featured by frequent spasms/tonic seizures and diffuse cortical dysplasia/periventricular nodular heterotopia. The three patients with biallelic missense variants presented mild partial epilepsy with favorable outcomes. Analysis of previously reported cases revealed that patients with biallelic null mutations presented significantly higher frequency of refractory seizures and earlier onset age of seizure than those with biallelic non-null mutations or with biallelic mutations containing one null variant. Significance This study suggested that SZT2 variants were potentially associated with partial epilepsy with favorable outcomes without NDD, expanding the phenotypic spectrum of SZT2. The genotype-phenotype correlation helps in understanding the underlying mechanism of phenotypic variation.